Solutions To Problems Arising In Agriculture In Uzbekistan In The Context Of The Digital Economy - Erkin, Shavqiev; Farkhod Fakhriddinovich, Ulugmurodov; Avazbek Sadullaevich, Karshiev; Ziyodulla, Rashidov (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2025)
This article explores challenges faced by Uzbekistan's agricultural sector in the context of the growing digital economy and proposes innovative solutions. It examines both macro-level issues, such as outdated infrastructure, inefficient resource management, and limited access to technology, and micro-level problems, including farm-level productivity, insufficient data-driven decision-making, and inadequate farmer education. The study emphasizes the role of digital tools, such as precision agriculture, IoT-based monitoring systems, and blockchain for supply chain transparency, in addressing these challenges. Additionally, it highlights the necessity of government policies, private sector collaboration, and capacity-building initiatives to accelerate the adoption of digital technologies in agriculture. By leveraging digital advancements, Uzbekistan can achieve sustainable agricultural growth and contribute to national food security and economic development.